Increased genetic diversity and prevalence of co-infection with Trypanosoma spp. in koalas (Phascolarctos cinereus) and their ticks identified using next-generation sequencing (NGS). - Amanda D Barbosa; Alexander W Gofton; Andrea Paparini; Annachiara Codello; Telleasha Greay; Amber Gillett; Kristin Warren; Peter Irwin; Una Ryan (PLoS ONE, 2017)
Infections with Trypanosoma spp. have been associated with poor health and decreased survival of koalas (Phascolarctos cinereus), particularly in the presence of concurrent pathogens such as Chlamydia and koala retrovirus. The present study describes the application of a next-generation sequencing (NGS)-based assay to characterise the prevalence and genetic diversity of trypanosome communities in koalas and two native species of ticks (Ixodes holocyclus and I. tasmani) removed from koala hosts. Among 168 koalas tested, 32.2% (95% CI: 25.2-39.8%) were positive for at least one Trypanosoma sp. Previously described Trypanosoma spp. from koalas were identified, including T. irwini (32.1%, 95% CI: 25.2-39.8%), T. gilletti (25%, 95% CI: 18.7-32.3%), T. copemani (27.4%, 95% CI: 20.8-34.8%) and T. vegrandis (10.1%, 95% CI: 6.0-15.7%). Trypanosoma noyesi was detected for the first time in koalas, although at a low prevalence (0.6% 95% CI: 0-3.3%), and a novel species (Trypanosoma sp. AB-2017) was identified at a prevalence of 4.8% (95% CI: 2.1-9.2%). Mixed infections with up to five species were present in 27.4% (95% CI: 21-35%) of the koalas, which was significantly higher than the prevalence of single infections 4.8% (95% CI: 2-9%). Overall, a considerably higher proportion (79.7%) of the Trypanosoma sequences isolated from koala blood samples were identified as T. irwini, suggesting this is the dominant species. Co-infections involving T. gilletti, T. irwini, T. copemani, T. vegrandis and Trypanosoma sp. AB-2017 were also detected in ticks, with T. gilletti and T. copemani being the dominant species within the invertebrate hosts. Direct Sanger sequencing of Trypanosoma 18S rRNA gene amplicons was also performed and results revealed that this method was only able to identify the genotypes with greater amount of reads (according to NGS) within koala samples, which highlights the advantages of NGS in detecting mixed infections. The present study provides new insights on the natural genetic diversity of Trypanosoma communities infecting koalas and constitutes a benchmark for future clinical and epidemiological studies required to quantify the contribution of trypanosome infections on koala survival rates.